PECULIARITIES OF TEACHING ENGLISH AMONG ADOLESCENT STUDENTS (Konferensiyalar | Conferences, 2024)
The abstract explores the multifaceted nature of teaching adolescents, focusing on the challenges and strategies involved in catering to their unique developmental needs, cognitive abilities, and socio-emotional well-being. Adolescents are characterized by their increasing autonomy, desire for relevance, and heightened emotional sensitivity, which necessitate tailored instructional approaches. Differentiation in teaching, specifically in the context of English language instruction, is emphasized as a means to accommodate the diverse learning styles and developmental trajectories of high school students. The abstract underscores the importance of considering developmental theories and processes in assessing both children and adolescents to ensure accurate evaluation and support. Additionally, it highlights the role of socio-emotional support in fostering a positive classroom environment conducive to adolescents' overall well-being and academic success. Through a comprehensive understanding of adolescent development and effective instructional practices, educators can better meet the diverse needs of adolescent learners in the classroom.